Scaled-up production of C-2 hydrocarbons by the oxidative coupling of methane over pelletized Na2WO4/Mn/SiO2 catalysts: Observing hot spots for the selective process - Lee, Jong Yeol; Jeon, Wonjin; Choi, Jae-Wook; Suh, Young-Woong; Ha, Jeong-Myeong; Suh, Dong Jin; Park, Young-Kwon (ELSEVIER SCI LTD, 2013)
The oxidative coupling of methane (OCM) to produce ethane and ethylene, valuable hydrocarbons, was scaled-up using differential, mid-scale, and bench-scale reactors with 0.030, 2.73, and 40 g of packed catalysts, respectively. Organic and inorganic binders, such as methylcellulose, Al2O3, MgO, and TiO2, were mixed with Na2WO4/Mn/SiO2 catalyst powder to produce catalyst pellets, and TiO2-mixed catalyst pellets exhibited the highest C-2 hydrocarbon yield despite the lowest active catalyst content. The formation of hot spots, which suppressed the selective conversion to C2 hydrocarbons by further oxidation to CO and CO2, was observed in the mid-and bench-scale reactors because of poor heat transfer. Inert-gas-diluted reactants and lower O-2 flow may inhibit the formation of hot spots and allow the development of industry-feasible OCM processes. (c) 2013 Elsevier Ltd. All rights reserved.
Keywords: DOPED TIO2 CATALYSTS; MN/NA2WO4/MGO CATALYSTS; SURFACE BASICITY; PERFORMANCE; LA2O3; TEMPERATURE; KINETICS; GAS